Med didaktiko slovenskega jezika in poezijo: ob 80-letnici Jožeta Lipnika - Marina Bajić; Jesenšek, Marko (2017)
When Slovene Language Didactics Meets Poetry: Jože Lipnikʼs 80th anniversary. Monograph When Slovene Language Didactics Meets Poetry is dedicated to Jože Lipnik’s 80th anniversary, a retired professor at University of Maribor’s Faculty of Education and former head of Department of Slavic Languages and Literature. 26 domestic and foreign researchers wrote their contributions in Slovene, Polish, Czech, Macedonian, Croatian, German and English languages. Slovene discussions contain Slovene-English synopsises and English abstracts, while discussions in other languages contain Slovene-English synopsises and Slovene abstracts. Contributions discuss the areas of language and literature didactics, linguistics and literature, dedicated to Lipnik’s diverse scientific, research and artistic (poetry) work.
Keywords: Jože Lipnik; jubilee; language didactics; literature didactics; linguistics; literary history; življenjski jubilej; didaktika jezika; didaktika književnosti; jezikoslovje; literarna zgodovina